Characterizations of certain Hankel transform involving Riemann–Liouville fractional derivatives - Upadhyay S.K.; Khatterwani K. (My University, 2025)
In this paper, the relation between two dimensional fractional Fourier transform and fractional Hankel transform is discussed in terms of radial functions. Various operational properties of Hankel transform and fractional Hankel transform are studied involving Riemann–Liouville fractional derivatives. The application of fractional Hankel transform is given in networks with time varying parameters. © 2019, SBMAC - Sociedade Brasileira de Matemática Aplicada e Computacional.